Associations of infectious disease-specific, electronic, and general health literacy among high school students with prevalent health challenges: a cross-sectional study - Qin, Jie; Gong, Yan; Hu, Ruijuan; Lou, Yifang; Xuan, Xiaoyan; Wang, Peng; Gong, Guangming (Frontiers in Public Health, 2025)
The interplay of infection-specific (IDSHL), electronic (eHL), and general health literacy (HL) in shaping adolescent health disparities during recurrent infections remains underexplored. This cross-sectional study mainly evaluated the levels and associations of IDSHL, eHL and HL among 10th–11th graders (n = 272) using validated instruments (IDSHLS, eHEALS, HLS-SF12) via anonymous questionnaires. Results revealed that 89.7% of participants reported prevalent health concerns, most notably mood (52.2%), sleep (51.8%), vision (47.8%), weight (34.5%) and gastrointestinal (28.3%) issues, with 66.5% engaging in risk behaviors such as physical inactivity (50.4%) and poor dietary habits (40.4%), while electronic new media overwhelmingly dominated health information acquisition. Literacy proficiency varied: 85.29% exhibited high IDSHL (mean ± SD: 23.23 ± 7.69), 51.1% in high eHL (28.22 ± 8.10) and 48.9% in high HL (34.81 ± 10.29). Binary logistic regression identified IDSHL as an independent HL predictor (OR = 10.28, 95% CI 1.79–59.14, p < 0.01) and revealed reciprocal eHL-HL associations (eHL → HL: OR = 23.31; HL → eHL: OR = 23.15; both p < 0.01). These findings highlight adolescents’ disproportionate health burdens, digital-focused information acquisition, literacy gaps, and preliminary evidence of a reciprocal IDSHL-eHL relationship within health literacy frameworks. The study advocates integrated interventions combining infection-specific education, digital health training, and behavior modification to address adolescent health disparities in prevention-focused digital healthcare systems.